An ESIPT based versatile fluorescent probe for bioimaging live-cells and E. coli under strongly acidic conditions. (5th October 2021) - Singla, Nancy; Ahmad, Manzoor; Dhiman, Sukhvinder; Kumar, Gulshan; Singh, Siloni; Verma, Shagun; Kaur, Satwinderjeet; Rashid, Muzamil; Kaur, Sukhraj; Luxami, Vijay; Singh, Prabhpreet; Kumar, Subodh
Abstract : A BTNN probe undergoes a 146 times increase in fluorescence intensity at 530 nm on lowering the pH from 7.0 to 2.0 and has been deployed for the bioimaging of MG-63 live cells and E. coli bacteria at different pH levels. Abstract : A 2-(2-hydroxyphenyl)benzothiazole based probe BTNN undergoes a drastic upsurge (∼146-fold, Φ = 69%) in fluorescence intensity (bright green, λ em 530 nm) on going from pH 7 to 2. MG-63 cells and E. coli bacteria internalize BTNN without toxicity and its fluorescence intensity is directly correlated to the pH in the cells/bacteria. This response to pH is instantaneous, reversible and stable for over a week. The protonation of the diethylamino nitrogen followed by efficient normal and excited state intramolecular proton transfer (ESIPT) processes of protonated BTNN are responsible for remarkable increase in fluorescence intensity and quantum yield under acidic conditions. Furthermore, polystyrene-BTNN thin films can be used for efficient detection of HCl vapour (2 ppm). This is first example where 2-(2-hydroxyphenyl)benzothiazole derivative can image strong acidic conditions.